2012
DOI: 10.1007/s13280-012-0310-5
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Response to Climatic Change: The Importance of the Cold Season

Abstract: Winter climate and snow cover are the important drivers of plant community development in polar regions. However, the impacts of changing winter climate and associated changes in snow regime have received much less attention than changes during summer. Here, we synthesize the results from studies on the impacts of extreme winter weather events on polar heathland and lichen communities. Dwarf shrubs, mosses and soil arthropods were negatively impacted by extreme warming events while lichens showed variable resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…In the past several decades, the peak flow of many rivers in North America, Europe, and Asia occurred approximately 30-40 days earlier (Arnell, 1999;Stewart et al, 2004); the snow cover duration was shortened for approximately 1 month (W. Zhang, Kang, et al, 2017). Earlier and slower snowmelt can also influence the ecological processes due to the changes in soil moisture and evapotranspiration (Bokhorst et al, 2012;Dunne et al, 2003). Earlier and slower snowmelt can also influence the ecological processes due to the changes in soil moisture and evapotranspiration (Bokhorst et al, 2012;Dunne et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the past several decades, the peak flow of many rivers in North America, Europe, and Asia occurred approximately 30-40 days earlier (Arnell, 1999;Stewart et al, 2004); the snow cover duration was shortened for approximately 1 month (W. Zhang, Kang, et al, 2017). Earlier and slower snowmelt can also influence the ecological processes due to the changes in soil moisture and evapotranspiration (Bokhorst et al, 2012;Dunne et al, 2003). Earlier and slower snowmelt can also influence the ecological processes due to the changes in soil moisture and evapotranspiration (Bokhorst et al, 2012;Dunne et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many vascular plants are severely damaged after winter warming events, as shown both by analyses of natural events and field experiments (Bokhorst et al . , , ; Bjerke et al . ; Cooper ).…”
Section: Introductionmentioning
confidence: 99%
“…The negative influence of the positive temperature values during winter months can be linked to the melting snow cover and the development of a thin ice cover, which can partially damage the previous year dwarf shrub branches. Bokhorst et al (2009Bokhorst et al ( , 2012 reported similar data, that dwarf shrubs in the Arctic area are negatively impacted by extreme warming events during winter.…”
Section: Discussionmentioning
confidence: 64%